Case Report: Identification of Multiple TERT and FGFR2 Gene Fusions in a Pineal Region Glioblastoma Case - Guo, Xing; Chen, Teng; Chen, Shiming; Song, Chao; Shan, Dezhi; Xu, Shujun; Xu, Shuo (Frontiers in Oncology, 2021)
As an oncogenic somatic variant, telomerase reverse transcriptase promoter (TERTp) mutations frequently observed in adult glioblastoma (GBM). Alternatively, we report the first case of glioblastoma with TERT amplification accompanied by multiple TERT and FGFR2 gene fusions instead of TERTp mutation. A 55-year-old woman presented with dizziness, headache, and diplopia for three weeks. Magnetic resonance imaging (MRI) demonstrated a heterogeneously enhancing lobulated mass centered in the pineal region. Partial tumor resection and ventriculoperitoneal shunt were achieved, and the residual tumor was then treated with standard radiation. The tumor was diagnosed as GBM, IDH-wild type, WHO grade Ⅳ, and the Ki67 proliferation index was high (30%~40%). Intriguingly, TERT amplification without TERTp mutation was identified via next generation sequencing (NGS). Further analysis revealed multiple TERT (TERT-NUBPL, MARCH6-TERT, and CJD4-TERT) and FGFR2 (CXCL17 -FGFR2, SIPA1L3-FGFR2, FGFR2 -SIPA1L3, and FGFR2- CEACAM1) gene fusions. After the surgery, the patient’s condition deteriorated rapidly due to the malignant nature of the tumor and she died with overall survival of 3 months. Our report provides the molecular clue for a novel telomerase activation and maintenance mechanism in GBM.